(3JUQaGJ GdeQjV eQV GdehJ (B:s (3OQGSI ebGQfI (B/s - (3GdeRhQj, MHjH EOQjS YjSis ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2015)
(3jJfGhd cJGH (B((3JUQaGJ GdeQjV eQV GdehJ (B: (3OQGSI ebGQfI(B) (3hGdPj bGe HJCdjag (B((3MHjH EOQjS YjSi GdeRhQj(B) (3aj MhGdj (B(198) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdCgdjI (B((3bGfhf eOfj(B)) (3eSJYQVG CHQR GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3eGgjI eQV GdehJ, GdaUd GdKGfj (B: (3EKHGJ UOhQ GdJUQa aj eQV GdehJ heOi JbjjO JUQaGJ GdeQjV, GdaUd GdKGdK (B: (3CMcGe JUQaGJ GdeQjV eQV GdehJ(B.s
(3HHdjhLQGajI (B: (3UaMI (B183-196.s
Keywords: (3GdCgdjI (B((3bGfhf eOfj(B)s; (3GdeQVis -- (3hVY bGfhfj, bhGfjf, EdN(B. s